Association Between Neighbourhood Food Environment And Dietary Quality Among Adolescents In Kuala Lumpur, Malaysia - Nurfarhana Norddin; Nik Norasma Che’Ya; Nur Adibah Mohidem; Nurzalinda Zalbahar (CellPress, 2025)
Indexed Publication (Tier 1)